PENERAPAN PEMROGRAMAN PYTHON DALAM MENENTUKAN WAKTU OVERHOUL KONDENSOR TURBIN UAP - Sulis Yulianto; Raihan Muhammad (Jurnal Konversi Energi dan Manufaktur, 2023)
Condensers as the main equipment and heat exchangers in a combined cycle power plant have a major effect to determine combined cycle efficiency. The condenser is used to transform saturated steam into water which will be reused in a combined cycle power plant. To acquire high performance, the condenser requires an overhaul plan and calculated performance. In this research, to determine a good overhaul plan, the python programming language with the linear regression method is used. The python programming language aims to predict the condenser when it must be overhauled. From the results of the research, it was found that there was an increase in the value of the cleanliness factor condenser before the overhaul. From 56.69% to 57.45% after the overhaul. After using linear regression in python programming on the distribution data from 2018 which was divided into three groups of analysis, it was found that the condenser must be overhauled on August 24, 2023.